POLARITAS DEIKSIS PERSONA NOVEL SHERLOCK HOLMES: SKANDAL DI BOHEMIA (TINJAUAN PRAGMATIK) - Pehala, Ilfan Askul (Sunan Kalijaga State Islamic University Yogyakarta, 2019)
This study aims to determine, analyze, and describe the person deixis and the polarity of the use of the deixis, based on the Yule deixis theory. The deixis analysis in this study is not only looking for the existing deixis persona but also looking at the correlation in the grammatical deixis category in lingual units. The analysis is then connected with the concepts of competence and performance in the linguisic deixis unit to see the concepts of language and thinking of the writers in this novel. It is all the basis of the novelty of this study. This study uses a qualitative descriptive design that is consistent with linguisic research. Data collection techniques were carried out through qualitative methods, that is, the method of distribution using the BUL technique or direct division of data into the lingual unit and the analysis of the Spradely ethnic method to determine the domain, taxonomy, and componential person deixis. The data in this research include the written lingual unit whose marker of reference and types indicates or is recorded as deixis. The main data source is a series of stories from Sir Arthur Conan Doyle’s Sherlock Holmes, particularly A Scandal in Bohemia which consists of three parts. The results of the analysis show that the persona in speech has other functions: as nominating, objective, and genitive markers. The polarity of the person deixis indirectly determines the concept of the author's competence and performance which unconsciously shapes the dominance and strength of the character that determines the centrality of the character and then also the storyline.